Firm responses to employment subsidies: a regression discontinuity approach to the 2012 Spanish labour market reform - Elisa Gamberoni; Katerina Gradeva; Sebastian Weber (European Central Bank (ECB), 2016)
This study focuses on the employment effect of a hiring subsidy available to firms with less than 50 employees, granted in the context of the 2012 Spanish labour market reform. Exploiting the arbitrary firm size threshold using regression discontinuity design, estimates show on average 2 percentage points higher employment growth for firms that became eligible for the scheme. However, tests and complementary regressions suggest that the higher employment growth for smaller firms in 2013 is driven by a 2010 reform, which imposes more stringent reporting requirements on larger firms. Accounting for this using difference-in-discontinuity regressions, we fail to find any significant effect of the subsidy on increasing employment of eligible firms. While our study suggests several pitfalls arising from size-contingent regulations, more data are needed to test for benecial long-term effects from the hiring subsidy in addressing duality of the Spanish labour market.
Keywords: C21; D22; E24; H25; 330; employment subsidies; firm response; labour market reforms; quasi-experiment; regression discontinuity design